A Concept Crystal Habit Phase Diagram and Data for Curcumin in Isopropanol: Classical Versus Non-Classical Crystallization - Mahmoud Ranjbar; Mayank Vashishtha; Gavin Walker; K. Vasanth Kumar (Crystals)
Cooling crystallization experiments of curcumin in isopropanol confirmed that curcumin can crystallize via classical or nonclassical pathways, depending on the levels of supersaturation and supercooling. Light microscopy analysis revealed that classical crystallization produces needle-shaped single crystals with an equilibrium habit, while nonclassical crystallization results in spherulitic mesocrystals. Through a series of experiments under various conditions, we developed a crystal habit phase diagram for curcumin in pure isopropanol. Presented here for the first time, this diagram illustrates the relationship between supersaturation, supercooling, and crystal habit, offering a valuable guide for controlling curcumin crystallization pathways.